Thesis web-based for [PPSUG] UiTM Perlis / Nurhusna Amira A. Rahim - A. Rahim, Nurhusna Amira (2019)
This study design for Centre of study Surveying Science and Geomatics, UiTM Cawangan, Perlis. Thesis Web-based is an activity carried out to maintain the optimum number or amount of each thesis, in this study, the thesis refers to the previous thesis management. The aim of this project is to record all the thesis information systematically for PPSUG in Uitm Cawangan Perlis. By applying web-based Geographic Information System (GIS) and programming language we were able to manage thesis management with linkage to all database, including the database of thesis, database of supervisor information and the map of the building plan for supervisor rooms and programming language; HTML, CSS and SQL to integrate data on the web. The target user of this system is more to geomatics students. The result will make way for an effective system integrating web-based GIS. The combination of web-based GIS and thesis, management system has many advantages which make the system more user-friendly and easy to access anytime and anywhere.